Supply and demand -making the most of export opportunities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Poor marketing and distribution frequently waste opportunities provided by increased or diversified agricultural production There are many examples where farmers have produced higher yields or cultivated new crops at their own expense and risk but...